Living Gymnosperms in Uttar Pradesh in India and their Economic Importance - Dr. V.P. Singh (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2020)
The paper presents a preliminary report on the distribution of Living Gymnosperms in Uttar Pradesh, State of India. As per the records available at BSA and exploration 19 species, 11 genera, 1 variety under 7 families have been recorded so for area under study. Economic uses of some gymnosperms are also given.